Additional file 1: Table S1. of The prevalence and impact of Babesia canis and Theileria sp. in free-ranging grey wolf (Canis lupus) populations in Croatia - Beck, Ana; Huber, Doroteja; Polkinghorne, Adam; Kurilj, Andrea; Benko, Valerija; Mrljak, Vladimir; ReljiÄ, Slaven; Kusak, Josip; Reil, Irena; Beck, Relja (Figshare, 2017)
Raw data for investigated wolves. (XLSX 27Â kb)